A stable Leifsonia xyli subsp. xyli GFP‐tagged strain reveals a new colonization niche in sugarcane tissues. (23rd June 2015) - Quecine, M. C.; Silva, T. M.; Carvalho, G.; Saito, S.; Mondin, M.; Teixeira‐Silva, N. S.; Camargo, L. E. A.; Monteiro‐Vitorello, C. B.
Abstract : Ratoon stunting disease (RSD), caused by the bacterium Leifsonia xyli subsp. xyli (Lxx), is one of the most economically important diseases of sugarcane worldwide. Because knowledge on the interaction of Lxx with its host at the microscopic level is limited, the development of tools to monitor Lxx during the colonization process could shed new light on the processes that control disease development. In this investigation, a transformation protocol was optimized and a mutant Lxx strain engineered that stably expressed the gfp gene in sugarcane tissues. In vitro, the growth of the mutant did not differ from that of the wild type. Also, plants inoculated with both strains showed comparable growth and development when analysed 180 days after inoculation (dai). Fluorescence microscopy of roots, stalks, meristems and leaf tissues of Lxx‐GFP‐inoculated plants was performed at 180 dai. In the leaves, Lxx‐tagged cells were observed within the xylem vessels as has been described before but, in addition, they were found in a new niche within the host tissues, in the mesophyll and in the bundle sheath cells surrounding the vascular system. This finding indicates that Lxx is able to move from the xylem to the parenchyma of the leaf cells. This first report of an Lxx mutant expressing a heterologous gene revealed that colonization of sugarcane by this pathogen is not limited to the xylem vessels as commonly reported.